Representações sociais sobre o climatério elaboradas por mulheres e sua importância nos cuidados em saúde - ANJOS, Raisa Ramos dos (2024)
Introduction: Climacteric is a biological phase that marks the transition from reproductive to non-reproductive life and occurs in women aged between 40 and 65 years, and is characterized by a physiological and progressive hormonal drop in estrogen and progesterone. Knowing the social representations (SR) created by women can help identify beliefs, behaviors, meanings, in addition to exploring the experiences of these women who experience the climacteric and the importance of SR in health care. Objective: To understand the social representations that women create about the climacteric and its importance in health care. Methodological path: This is a qualitative study, based on the Theory of Social Representations in its dimensional approach, carried out in the primary care department in two units, in the second half of 2023. The sample was composed of 22 women through non-standard sampling. probabilistic for convenience and defined by theoretical saturation. Women between 40 and 65 years of age who reported signs and symptoms of menopause were included and those who stopped menstruating before the age of 40 were excluded. A semi-structured interview was used as a data collection instrument, containing sociodemographic data and guiding questions and a field diary. The data was organized with the help of the IRaMuTeQ software and lexical analysis, Hierarchical Descent Classification (CHD) and similarity analysis were performed. Results: From the CHD, the corpus was constituted into four classes: Perceiving symptoms and the need for health care (information or knowledge); Living with the climacteric: life change (image/field of representation); Vasomotor symptoms (image/field of representation) and Health care attitudes (positioning or attitude). Associated with the similarity analysis, it was observed that the social representations created by women help in understanding what they are experiencing in the new phase of life, in identifying the symptoms as typical of the climacteric and in taking health care actions. Conclusion: The content prepared by women about the climacteric leads to the search for health care, with the search for health services being the main attitude. In this context, the professional who provides care has an important role, as their care and conduct may determine the outcome of the care process. By knowing the SR of the climacteric, health professionals can implement forms of care using comprehensive and planned approaches that favor autonomy so that women can make efficient choices regarding their health.